Pengaruh Persistensi Laba, Struktur Modal, Ukuran Perusahaan, Risiko Sistematis Dan Alokasi Pajak Antar Periode Terhadap Kualitas Laba - Citra Zia; Abdul Malik (Universitas Serang Raya, 2022)
This study aims to determine the effect of earnings persistence, capital structure, firm size, systematic risk and inter-period tax allocation on earnings quality in food and beverage companies listed on the Indonesia Stock Exchange. The study was conducted using data processing methods namely multiple linear regression and the data used are secondary data in the form of financial statements in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2017. The sample used was 6 companies using purposive sampling method and the data was analyzed using SPSS version 23. Based on the results of the study it can be concluded that: 1). Earnings persistence affects the quality of earnings, 2). Capital structure does not affect the quality of earnings, 3). Company size does not affect the quality of earnings, 4). Systematic risk affects the quality of earnings, 5). Tax allocation between periods does not affect the quality of earnings. Keywords: